2012
DOI: 10.1038/cmi.2012.11
|View full text |Cite
|
Sign up to set email alerts
|

TLR2 signaling subpathways regulate TLR9 signaling for the effective induction of IL-12 upon stimulation by heat-killed Brucella abortus

Abstract: Brucella abortus is a Gram-negative intracellular bacterium that induces MyD88-dependent IL-12 production in dentritic cells (DCs) and a subsequent protective Th1 immune response. Previous studies have shown that the Toll-like receptor 2 (TLR2) is required for tumor-necrosis factor (TNF) production, whereas TLR9 is responsible for IL-12 induction in DCs after exposure to heat-killed Brucella abortus (HKBA). TLR2 is located on the cell surface and is required for optimal microorganism-induced phagocytosis by in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 46 publications
1
14
0
Order By: Relevance
“…These data also agree with a previous report indicating that p38 inhibitors temper IL-12p40 responses, whereas an ERK1/2 inhibitor significantly increases IL-12p40 in heat-killed B. abortus-stimulated DCs. 70 Taken together, these findings suggest that rBCSP31 may activate several innate immune signaling pathways, culminating in cytokine production. In addition, we observed that the phosphorylation of MAPK in response to rBCSP31 is mediated primarily by TLR2 and TLR4.…”
Section: Discussionmentioning
confidence: 89%
“…These data also agree with a previous report indicating that p38 inhibitors temper IL-12p40 responses, whereas an ERK1/2 inhibitor significantly increases IL-12p40 in heat-killed B. abortus-stimulated DCs. 70 Taken together, these findings suggest that rBCSP31 may activate several innate immune signaling pathways, culminating in cytokine production. In addition, we observed that the phosphorylation of MAPK in response to rBCSP31 is mediated primarily by TLR2 and TLR4.…”
Section: Discussionmentioning
confidence: 89%
“…Furthermore, no apparent cooperative interplay was observed between TLR2-TLR9 or TLR6-TLR9 receptors concerning bacterial load in infected mice. However, crosstalk between TLR2 and TLR9 in DCs stimulated with HKBa has been reported in vitro [37]. In such a scenario, TLR2 can drive the TLR9 response in DCs upon HKBa stimulation, leading to IL-12 production [37].…”
Section: Discussionmentioning
confidence: 99%
“…The different regulatory mechanisms affected by EH to control IL-10 expression may be due to differences in crosstalk between EH to the signaling pathways downstream of different TLRs. 28 Regardless of whether mice were challenged with LPS or PGN, DXM had a small impact on anti-inflammatory IL-10 expression. In contrast, EH enhances IL-10 secretion significantly in both LPS-and PGN-challenged mouse models.…”
Section: Discussionmentioning
confidence: 99%